230 Acute Bowel Obstruction - Are We in The Loop?. (12th October 2021) - Tan, J R; Mann, K
Abstract: Aim: Acute bowel obstruction (ABO) is a common surgical emergency associated with high mortality and morbidity. The aim of this audit is to compare the quality of local management of ABO against recommendations set by the NCEPOD. Method: A prospective audit of all patients presented with ABO over 8 weeks from February 2020 at a tertiary centre. Data was collected from electronic records. Results: 34 patients were reviewed with a mean age of 69.8 years. 24 presented with small bowel obstruction and 10 with large bowel obstruction. 25 (73.5%) patients had a CT with IV contrast with a median time to scan of 5 hours. 25 (73.5%) patients were reviewed by consultants within 14 hours and 5/7 high-risk cases were discussed within an hour. Adequate pain control was achieved in 26 (76.5%) cases. All patients had BMI recorded and 29 (85.3%) had MUST score documented. 16/25 (64.0%) patients aged above 64 had their frailty score assessed and 11/25 (44.0%) received geriatrician input. 32 (94.1%) patients had their treatment plan discussed with them and family was informed in 19 (55.9%) cases. 19 (55.9%) patients underwent emergency operation and there was a delay in access to surgery in 7/19 (36.8%) cases. Morbidity and mortality risk was calculated in 3/19 (15.8%) cases. Conclusions: This audit has highlighted numerous positive management measures but also the need for improved radiological resources, better emergency capacity planning and risk assessment. There needs to be a focus on predicting outcomes, especially in the elderly and setting limitations and expectations before surgery.